FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Devaki, Alfatur (LLDIKTI Wilayah X, 2017)
The main purpose of investors from investing in the stock of companies is wealth increase which is achieved through stock return. Therefore, investors need to know about factors which affect on stock return in order to get the expected rate of stock return. This study aims to examine the effect of the fundamental factors which are measured by dividend payout ratio and price to earnings ratio, and the effect of the technical factor which is measured by beta on stock return on companies listed in LQ 45 in Indonesia Stock Exchange 2013-2015. The population of this research was all of companies listed in LQ 45 in Indonesia Stock Exchange, and the sampel consisted of twenty one companies. The analysis was conducted by using multiple linear regression. The results indicated that the dividend payout ratio did not have effect on stock return, while price to earnings ratio and beta affected on stock return.So, investors can consider of price to earnings ratio and beta variables to predict the expected rate of stock return.